German translation and psychometric testing of the Postconcussion Symptom Inventory for adolescents in self-report (PCSI-SR13) and parent-report (PCSI-P) - Dagmar A. Timmermann; Marina Zeldovich; Ugne Krenz; Ivana Holloway; Katrin Cunitz; Inga K. Koerte; Anna Buchheim; Christel Salewski; Gerard A. Gioia; Nicole von Steinbuechel (PLoS ONE, 2025)
Adolescents are at an increased risk of sustaining a traumatic brain injury (TBI), which is associated with physical, cognitive, and/or emotional impairments, the so-called post-concussion symptoms (PCS). To fill the gap of German-language instruments for the age-appropriate assessment of PCS, the current study presents the translation, linguistic validation, and psychometric examination of two versions of the Postconcussion Symptom Inventory (PCSI) for adolescents (PCSI-SR13; 21 items) and their parents (PCSI-P; 20 items). Translation included iterative forward and backward translations and cognitive debriefings (CD). A total of 117 adolescents (aged 13–17 years) after TBI (3 months up to 10 years after injury) and 111 parents completed the PCSI. Both German versions were compared descriptively with the corresponding English versions. Analyses were conducted at the item and scale level. Confirmatory factor analyses (CFA) were performed, and internal consistency was examined using Cronbach’s α and McDonald’s ω. Convergent validity testing used Spearman’s ρ correlations with the Rivermead Post-Concussion Symptoms Questionnaire (RPQ). Cohen’s κ at the item level and intraclass correlation coefficients (ICC) were calculated to assess adolescent-parent agreement. The original four-factor structure could be replicated for the PCSI-SR13, but not for the PCSI-P. Internal consistency was good to excellent (≥ 0.80). Correlations (ρ ≥ 0.57) indicated a strong association with the RPQ. At the item level, the adolescent-parent agreement was fair to moderate (κ: 0.14–0.58). At the subscale level, interpretation of the ICC (ICC: 0.51–0.71) was limited due to the wide CI95%. In general, the psychometric properties support the applicability of the PCSI-SR13 and the PCSI-P for assessing PCS in German-speaking adolescents in the subacute and chronic phase after TBI. However, given the lack of factorial validity of the PCSI-P and the discrepancies between adolescents’ and parents’ ratings, self-report is recommended.